A biaxially oriented polypropylene aluminized label film and preparation method thereof

By adding ethylene-propylene-5-vinyl-2-norbornene terpolymer to the aluminized layer of the bidirectional tensile polypropylene aluminum-plated label film, and adding modified pearlite masterbatch and maleic anhydride-homopolypropylene graft copolymer to the intermediate layer, the problem of insufficient surface tension of the aluminum-plated layer of the traditional label film is solved, and the effects of strong adhesion and corona attenuation are achieved.

CN119459080BActive Publication Date: 2025-04-15GUANGDONG DECRO PACKAGE FILMS
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510053567.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-15
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The surface tension of the traditional bidirectional tensile polypropylene aluminum-plated label film is insufficient, resulting in frequent occurrence of aluminum layer not firmly adhesion and aluminum loss, and the corona decay of the aluminum layer is too fast, affecting subsequent coating and printing work.

Method used

The surface tension and durability of the aluminum-copolymer are added to the aluminized layer of the bidirectional stretched polypropylene aluminum-coated label film, and 10-20 wt% of the modified pearlite masterbatch and 4-7 wt% of the maleic anhydride-homopolypropylene graft copolymer are added to the intermediate layer to improve the surface tension and durability of the aluminum-coated layer.

Benefits of technology

The surface tension of the aluminum-coated layer is greatly improved and durable, ensuring strong adhesion of the aluminum layer, reducing aluminum loss, and delaying the corona attenuation of the aluminum layer, improving the stability of subsequent processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to a biaxially oriented polypropylene aluminized label film and a preparation method thereof, and belongs to the technical field of aluminized label films. The biaxially oriented polypropylene aluminized label film comprises an aluminized layer, an intermediate layer and a lower surface layer arranged in sequence; the aluminized layer comprises copolymerized polypropylene and 15-25wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer; the content of 5-vinyl-2-norbornene in the ethylene-propylene-5-vinyl-2-norbornene terpolymer is 4.0-4.5mol; the intermediate layer comprises homopolymerized polypropylene, 10-20wt% modified pearlescent masterbatch and 4-7wt% maleic anhydride-homopolymerized polypropylene graft copolymer. The biaxially oriented polypropylene aluminized label film of the present invention has a large surface tension of the aluminized layer and a long-lasting surface tension through the coordinated design of the aluminized layer and the intermediate layer, and the aluminum layer formed on the surface of the aluminized layer after the film is vacuum-deposited has strong adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aluminized label films, in particular to a biaxially oriented polypropylene aluminized label film and a preparation method thereof. Background Art

[0002] Biaxially oriented polypropylene (BOPP) aluminized label film is usually white opaque BOPP film. When used, the biaxially oriented polypropylene aluminized label film is first vacuum-deposited (aluminized) to form an aluminum layer on the surface of the aluminized layer of the biaxially oriented polypropylene aluminized label film, so that the film has a metallic luster. Then, it is made into a wraparound label or self-adhesive label through coating, printing and other processes. It is widely used in the labeling of polyester bottles and spray bottles, giving the products a decorative and anti-counterfeiting effect.

[0003] However, the traditional biaxially oriented polypropylene aluminized label film has insufficient surface tension of the aluminized layer. After vacuum evaporation, the aluminum layer on the surface of the aluminized layer is prone to poor adhesion and aluminum falling off. Furthermore, even after the aluminum layer is attached, the corona of the aluminum layer decays too quickly, affecting subsequent coating and printing work. Summary of the invention

[0004] Based on this, the object of the present invention is to provide a biaxially oriented polypropylene aluminized label film and a preparation method thereof, wherein the aluminized layer of the biaxially oriented polypropylene aluminized label film has a large surface tension and a long-lasting surface tension, and the aluminum layer formed on the surface of the aluminized layer after the film is vacuum evaporated (aluminized) has strong adhesion.

[0005] To achieve the above object, the present invention adopts the following technical solutions:

[0006] The invention provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence; the aluminized layer comprises copolymerized polypropylene and 15-25wt% of ethylene-propylene-5-vinyl-2-norbornene terpolymer; the content of 5-vinyl-2-norbornene in the ethylene-propylene-5-vinyl-2-norbornene terpolymer is 4.0-4.5mol%; the intermediate layer comprises homopolymerized polypropylene, 10-20wt% of modified pearlescent masterbatch and 4-7wt% of t% maleic anhydride-homopolypropylene graft copolymer; the modified pearlescent masterbatch comprises homopolypropylene and 75-85wt% modified inorganic filler; the modified inorganic filler is obtained by coating the surface of calcium carbonate with a polyethylene glycol monomethyl ether grafted polypropylene copolymer, the polyethylene glycol monomethyl ether grafted polypropylene copolymer is synthesized from a maleic anhydride-homopolypropylene graft copolymer and polyethylene glycol monomethyl ether, and the grafting rate of the polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 35-45%.

[0007] The biaxially oriented polypropylene aluminized label film of the present invention adds the ethylene-propylene-5-vinyl-2-norbornene terpolymer to the aluminized layer, which is beneficial to blocking the migration of the intermediate layer substances to the surface of the aluminized layer. The modified pearlescent masterbatch and the maleic anhydride-homopolymerized polypropylene graft copolymer are added to the intermediate layer without introducing small molecular substances, which is beneficial to preventing the migration of the intermediate layer substances to the aluminized layer. Through the coordinated design of the aluminized layer and the intermediate layer, the surface tension of the aluminized layer of the biaxially oriented polypropylene aluminized label film is large and the surface tension is long-lasting. The aluminum layer formed on the surface of the aluminized layer after the film is vacuum evaporated (aluminized) has strong adhesion and is not prone to aluminum shedding. In addition, the surface tension of the aluminum layer is large and the surface tension is long-lasting, which is beneficial to subsequent coating, printing and other work.

[0008] The biaxially oriented polypropylene aluminized label film of the present invention, the intermediate layer comprises homopolypropylene, 10-20wt% modified pearlescent masterbatch and 4-7wt% maleic anhydride-homopolypropylene graft copolymer, the three of which are structurally stable in the intermediate layer and are not easy to migrate to the aluminizable layer, thereby preventing the polar groups on the surface of the aluminizable layer from being covered, thereby preventing the problem of significantly reducing the surface tension of the aluminizable layer after the film is stored for a period of time, thereby affecting the subsequent aluminizing processing.

[0009] The present invention adds 10-20wt% of modified pearlescent masterbatch to the intermediate layer, which can effectively improve the situation that the surface tension of the conventional biaxially oriented polypropylene aluminized label film in the aluminizable layer obviously decays (that is, the surface tension of the aluminizable layer is not persistent), and the surface tension of the aluminum layer formed after aluminizing the surface of the aluminizable layer obviously decays (that is, the surface tension of the aluminum layer is not persistent). The modified pearlescent masterbatch added to the middle layer of the present invention is different from the conventionally used pearlescent masterbatch. Due to the difference in the surface modification technology of calcium carbonate, the effective components of the conventionally used pearlescent masterbatch are mainly small molecular substances such as small molecular fatty acids, small molecular esters, and small molecular alcohols that are coated on the surface of calcium carbonate. However, these small molecular substances only exist on the surface of calcium carbonate particles through physical action and are unstable in combination with the surface of calcium carbonate. As time goes by, these small molecular substances will migrate to the surface of the aluminizable layer, further embedding the polar groups on the surface of the aluminizable layer. Moreover, the biaxially oriented polypropylene aluminized label film is usually subjected to corona treatment before aluminizing, which will further aggravate the migration of small molecular substances and cover the polar groups generated on the surface of the aluminizable layer after the corona treatment, resulting in extremely low surface tension on the surface of the aluminizable layer (especially after the film has been stored for a period of time), affecting the subsequent processing of aluminizing. The present invention takes into account the shortcomings of conventional pearlescent masterbatch and designs a modified pearlescent masterbatch to effectively improve the above problems. The modified pearlescent masterbatch of the present invention comprises homopolymerized polypropylene and 75-85wt% of modified inorganic filler. The modified inorganic filler is obtained by coating the surface of calcium carbonate with polyethylene glycol monomethyl ether grafted polypropylene copolymer (i.e., the surface of calcium carbonate is coated with the polyethylene glycol monomethyl ether grafted polypropylene copolymer). After the surface of calcium carbonate is coated with the polyethylene glycol monomethyl ether grafted polypropylene copolymer, since the polyethylene glycol monomethyl ether chain segment contains a large number of hydrophilic groups, it can be bonded with the groups on the surface of calcium carbonate to form chemical bonds, so that the polyethylene glycol monomethyl ether grafted polypropylene copolymer can stably coat the surface of calcium carbonate and is not easy to migrate. At the same time, since the polyethylene glycol monomethyl ether grafted polypropylene copolymer The grafted polypropylene copolymer is synthesized from a maleic anhydride-homopolymerized polypropylene graft copolymer and polyethylene glycol monomethyl ether. During the synthesis process, polyethylene glycol monomethyl ether undergoes an esterification reaction with a maleic anhydride group to form a lipophilic group, so that the polyethylene glycol monomethyl ether grafted polypropylene copolymer has a lipophilic group. The lipophilic group on the polyethylene glycol monomethyl ether grafted polypropylene copolymer can physically entangle the molecular chain with the homopolymerized polypropylene in the intermediate layer, further avoiding the occurrence of migration, making the structure of the intermediate layer stable, and preventing small molecular substances from migrating to the aluminum-platable layer, thereby preventing the polar groups on the surface of the aluminum-platable layer after the corona treatment of the surface of the covering film, and preventing the aluminum-platable layer itself or the aluminum layer formed after aluminum plating on the surface of the aluminum-platable layer from having a low surface tension after being stored for a period of time, thereby affecting subsequent processing.The content of the modified pearlescent masterbatch in the intermediate layer is 10-20wt%. If the content of the modified pearlescent masterbatch in the intermediate layer is lower than 10wt%, it cannot maintain the surface tension of the aluminum-platable layer itself or the aluminum layer formed after aluminum plating on the surface of the aluminum-platable layer, and the surface tension cannot be maintained long-lasting. If the content of the modified pearlescent masterbatch in the intermediate layer is higher than 20wt%, excessive addition may destroy the directional arrangement of the homopolypropylene molecules in the intermediate layer, resulting in a decrease in the tensile strength of the film.

[0010] The present invention limits the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer to 35-45%, so that the surface tension of the aluminum-platable layer itself or the aluminum layer formed after aluminum plating on the surface of the aluminum-platable layer of the biaxially oriented polypropylene aluminum-plated label film is best maintained. If the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is lower than 35%, it will not have the effect of maintaining the surface tension of the aluminum-platable layer itself or the aluminum layer formed after aluminum plating on the surface of the aluminum-platable layer high and lasting surface tension; if the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is higher than 45%, too many polyethylene glycol monomethyl ether segments will destroy the original molecular chain arrangement and crystal structure of homopolypropylene, resulting in a decrease in the mechanical properties of the film.

[0011] The present invention adds 4-7wt% of maleic anhydride-homopolypropylene graft copolymer to the intermediate layer, which can improve the dispersibility and compatibility of the modified pearlescent masterbatch and homopolypropylene in the intermediate layer. The maleic anhydride-homopolypropylene graft copolymer has a polar group at one end and a non-polar group at the other end, which can combine the modified pearlescent masterbatch with the homopolypropylene to improve the mechanical properties and the dispersibility of the modified pearlescent masterbatch in the homopolypropylene. If the content of the maleic anhydride-homopolypropylene graft copolymer in the intermediate layer is less than 4wt%, the effect of improving the mechanical properties cannot be achieved; if the content of the maleic anhydride-homopolypropylene graft copolymer in the intermediate layer is higher than 7wt%, the molecular chains of the substances in the intermediate layer will be entangled to a certain extent, causing the shear viscosity of the melt to increase, affecting the smoothness of production.

[0012] The biaxially oriented polypropylene aluminized label film of the present invention is also designed for an aluminized layer, wherein the aluminized layer comprises copolymerized polypropylene and 15-25wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer. The aluminized layer can play a role in blocking the migration of the intermediate layer material, which is beneficial to slowing down the attenuation rate of the surface tension of the aluminized layer, and ensuring the strong adhesion of the aluminum layer formed after aluminizing and the coating formed by subsequent processing.

[0013] The present invention can play a role in blocking the migration of the intermediate layer material by adding ethylene-propylene-5-vinyl-2-norbornene terpolymer to the aluminum-platable layer, and is conducive to maintaining the surface tension of the aluminum-platable layer. The ethylene-propylene-5-vinyl-2-norbornene terpolymer added to the aluminum-platable layer contains a cyclic norbornene structure, has large steric hindrance, belongs to a non-crystalline unit, can be filled into the amorphous region of the copolymerized polypropylene with high crystallinity, and through the joint action of the crystalline region and the non-crystalline region, the interaction force in the process of blending the ethylene-propylene-5-vinyl-2-norbornene terpolymer and the copolymerized polypropylene is improved, which is conducive to reducing the gap between the molecular chain of the ethylene-propylene-5-vinyl-2-norbornene terpolymer and the molecular chain of the copolymerized polypropylene, and finally plays a certain role in blocking the migration of the intermediate layer material, so that the polar groups generated by the aluminum-platable layer are not easily covered. Furthermore, the synthetic monomer 5-vinyl-2-norbornene in the ethylene-propylene-5-vinyl-2-norbornene terpolymer has two double bonds, one of which participates in the copolymerization reaction to allow 5-vinyl-2-norbornene to enter the molecular chain of the ethylene-propylene-5-vinyl-2-norbornene terpolymer, and the other double bond becomes a hanging side group of the molecular chain of the ethylene-propylene-5-vinyl-2-norbornene terpolymer. After corona treatment, the hanging side group can effectively improve the durability of the surface tension of the aluminum-platable layer, which is beneficial to slowing down the surface tension decay rate and ensuring the adhesion of the aluminum layer formed after aluminum plating. The content of the ethylene-propylene-5-vinyl-2-norbornene terpolymer in the aluminum-platable layer is 15-25wt%. If the content of the ethylene-propylene-5-vinyl-2-norbornene terpolymer in the aluminum-platable layer is lower than 15wt%, it cannot effectively block the migration of the intermediate layer material, and the effect of improving the surface tension and durability of the aluminum-platable layer is not obvious. The surface tension of the aluminum layer formed after aluminum plating on the surface of the aluminum-platable layer of the film is not durable. If the content of the ethylene-propylene-5-vinyl-2-norbornene terpolymer in the aluminum-platable layer is higher than 15wt%, the introduction of too many ring structures will increase the steric hindrance effect of the copolymerized polypropylene molecular chain, so that the movement of the molecular chain is restricted, resulting in a decrease in the mechanical properties of the film.

[0014] The present invention limits the content of 5-vinyl-2-norbornene in the ethylene-propylene-5-vinyl-2-norbornene terpolymer to 4.0-4.5 mol%. Selecting the ethylene-propylene-5-vinyl-2-norbornene terpolymer within this content range is conducive to obtaining better performance of blocking the migration of intermediate layer substances, while ensuring the maintenance of the surface tension of the aluminum-platable layer. If the content of 5-vinyl-2-norbornene in the ethylene-propylene-5-vinyl-2-norbornene terpolymer is lower than 4.0 mol%, it will not have a good effect of blocking the migration of intermediate layer substances, and the surface tension and durability of the aluminum-platable layer of the film itself or the aluminum layer formed after aluminum plating on the surface of the aluminum-platable layer cannot be significantly improved; if the content of 5-vinyl-2-norbornene in the ethylene-propylene-5-vinyl-2-norbornene terpolymer is higher than 4.5 mol%, due to the rigid structure of norbornene, too much norbornene will make the film brittle, resulting in a decrease in the mechanical properties of the film.

[0015] Furthermore, in the aluminum-platable layer, the preparation method of the ethylene-propylene-5-vinyl-2-norbornene terpolymer is: using phosphinimine semi-titanocenes as the main catalyst, methylaluminoxane as the co-catalyst, and ethylene, propylene and 5-vinyl-2-norbornene as monomers for copolymerization to obtain the ethylene-propylene-5-vinyl-2-norbornene terpolymer. The ethylene-propylene-5-vinyl-2-norbornene terpolymer can be synthesized by using phosphinimine semi-titanocenes as the main catalyst, methylaluminoxane as the co-catalyst, and ethylene, propylene and 5-vinyl-2-norbornene as the three monomers for copolymerization; of course, the above method does not represent a limitation on the preparation method of the ethylene-propylene-5-vinyl-2-norbornene terpolymer.

[0016] Furthermore, in the aluminum-platable layer, the melt index of the ethylene-propylene-5-vinyl-2-norbornene terpolymer is 8-12 g / 10 min (measurement conditions: 230° C., 2.16 kg), the melting point of the ethylene-propylene-5-vinyl-2-norbornene terpolymer is 108-120° C., and the number average molecular weight of the ethylene-propylene-5-vinyl-2-norbornene terpolymer is (2.5-5)×10 4. By controlling the melt index, melting point and number average molecular weight of the ethylene-propylene-5-vinyl-2-norbornene terpolymer within the above range, it is beneficial to improve the performance of the aluminum-platable layer in blocking the migration of the intermediate layer material and maintain the surface tension of the aluminum-platable layer. In addition, the ethylene-propylene-5-vinyl-2-norbornene terpolymer has a suitable number average molecular weight, which is beneficial to improve its interaction force during the blending process with copolymerized polypropylene, and is beneficial to reduce the gap between it and the copolymerized polypropylene molecular chain. Through the joint action of the crystalline region and the non-crystalline region, it finally has a barrier effect on the migration of the intermediate layer material, making it difficult for the polar groups generated by the aluminum-platable layer to be covered. If the number average molecular weight of the ethylene-propylene-5-vinyl-2-norbornene terpolymer is too low, the interaction force thereof during the blending process with the copolymerized polypropylene is small, which is not conducive to reducing the gaps between the molecular chains and fails to achieve the effect of improving the performance of the aluminum-plated layer in blocking the migration of the intermediate layer material; if the number average molecular weight of the ethylene-propylene-5-vinyl-2-norbornene terpolymer is too high, the ethylene-propylene-5-vinyl-2-norbornene terpolymer is likely to have an excessively high melt viscosity, affecting the smoothness of production.

[0017] Furthermore, in the aluminum-platable layer, the melt index of the copolymerized polypropylene is 6-10 g / 10 min (measurement conditions: 230° C., 2.16 kg), and the copolymerized polypropylene is a random ethylene-propylene copolymer.

[0018] Furthermore, in the intermediate layer, the preparation method of the polyethylene glycol monomethyl ether grafted polypropylene copolymer is: using a melt grafting method, dicumyl peroxide as an initiator and acetone as a solvent, adding it to homopolypropylene, using a high-speed mixer to heat and stir, grafting maleic anhydride onto homopolypropylene, and obtaining a maleic anhydride-homopolypropylene grafted copolymer; then adding the maleic anhydride-homopolypropylene grafted copolymer and polyethylene glycol monomethyl ether into a twin-screw extruder to synthesize the polyethylene glycol monomethyl ether grafted polypropylene copolymer. The polyethylene glycol monomethyl ether grafted polypropylene copolymer can be synthesized by the above scheme; of course, the above method does not represent a limitation on the preparation method of the polyethylene glycol monomethyl ether grafted polypropylene copolymer.

[0019] Furthermore, in the intermediate layer, the modified inorganic filler is prepared by treating 3-5wt% polyethylene glycol monomethyl ether grafted polypropylene copolymer as a filler surface treatment agent and 95-97wt% calcium carbonate as a filler in a high-speed mixer. After being treated in the high-speed mixer, the polyethylene glycol monomethyl ether grafted polypropylene copolymer can be coated on the surface of the calcium carbonate; of course, the above method does not represent a limitation on the preparation method of the modified inorganic filler.

[0020] Furthermore, in the intermediate layer, the preparation method of the maleic anhydride-homopolypropylene graft copolymer is: using a melt grafting method, dicumyl peroxide as an initiator and acetone as a solvent, adding them to homopolypropylene, using a high-speed mixer to heat and stir, grafting maleic anhydride onto the homopolypropylene, and obtaining the maleic anhydride-homopolypropylene graft copolymer.

[0021] Furthermore, in the middle layer, the particle size of the calcium carbonate is 0.5-1.5 μm, and preferably 0.8-1.3 μm in order to balance the foaming effect and cost.

[0022] Furthermore, in the intermediate layer, the melt index of the modified pearlescent masterbatch is 14-18 g / 10min (measurement conditions: 230°C, 2.16kg).

[0023] Furthermore, in the intermediate layer, the melt index of the maleic anhydride-homopolypropylene graft copolymer is 40-50g / 10min (measurement conditions: 230°C, 2.16kg). The maleic anhydride-homopolypropylene graft copolymer has a large melt index, which can reduce the viscosity of the homopolypropylene melt and improve the dispersibility of the modified pearlescent masterbatch in the homopolypropylene. If the melt index of the maleic anhydride-homopolypropylene graft copolymer is lower than 40g / 10min, it will not improve the dispersibility of the modified pearlescent masterbatch. If the melt index of the maleic anhydride-homopolypropylene graft copolymer is higher than 50g / 10min, it is not conducive to the uniform distribution of the modified pearlescent masterbatch in the homopolypropylene, which is easy to cause a decrease in the mechanical properties of a local position.

[0024] Furthermore, the lower surface layer includes homopolymer polypropylene and 1-5wt% anti-adhesion masterbatch. Adding an appropriate amount of anti-adhesion masterbatch to the lower surface layer is beneficial to increasing the smoothness of winding and unwinding the biaxially oriented polypropylene aluminized label film. If the content of the anti-adhesion masterbatch in the lower surface layer is lower than 1wt%, it will not have an effective anti-adhesion effect; if the content of the anti-adhesion masterbatch in the lower surface layer is higher than 5wt%, the anti-adhesion agent is likely to fall off during the production process, resulting in contamination of the guide roller and affecting the appearance of the product.

[0025] Furthermore, the effective component of the anti-adhesion masterbatch is at least one of silicon dioxide, talc and calcium carbonate, and the particle size of the effective component of the anti-adhesion masterbatch is 3-6 μm, preferably 4-5 μm in order to take into account the thickness of the lower surface layer and the problem of shedding.

[0026] Furthermore, the homopolypropylene in the middle layer, the homopolypropylene in the modified pearlescent masterbatch, and the homopolypropylene in the lower surface layer have a melt index of 3-8 g / 10 min (measurement conditions: 230° C., 2.16 kg).

[0027] The present invention also provides a method for preparing a biaxially oriented polypropylene aluminized label film, comprising the following steps:

[0028] Step 1: Batching and plasticization: The proportion of each layer of raw materials is set in the control system of the biaxial stretch film production line, and then the batching system will automatically transport the dried raw materials of each layer to each layer extruder according to the input ratio. After melting and plasticizing in each layer extruder, the melt enters the die head through the runner and distributor;

[0029] Step 2: Slice casting: After being extruded through the die, the melt immediately contacts the cooling roller to form a thick sheet;

[0030] Step 3: Longitudinal stretching: The thick sheet is heated to the set temperature by multiple sets of preheating rollers, and then begins to be longitudinally stretched and then shaped;

[0031] Step 4: Transverse stretching: After preheating the thick sheet that has been longitudinally stretched to the set temperature, transverse stretching begins, and after transverse stretching, shaping and cooling are performed;

[0032] Step 5: Traction and reeling: The multi-layer film from the transverse stretching unit enters the traction unit, and after thickness measurement and corona treatment, enters the reeling unit to obtain a parent roll;

[0033] Step 6: Slitting: Slitting the aged mother roll to obtain film rolls of specified width and length.

[0034] As a preferred scheme, in the above process, the melt extrusion temperature of the aluminum-plated layer is: 200-260℃; the melt extrusion temperature of the middle layer and the lower surface layer is: 230-260℃; in the process of the melt contacting the cooling roller, the temperature of the chilling water and the chilling roller is: 15-50℃; the temperature of the longitudinal stretching zone is: 90-130℃; the temperature of the transverse stretching zone is: 155-165℃; the longitudinal stretching ratio is 4.5-5.5 times; the transverse stretching ratio is: 8-10 times; the corona power factor of the aluminum-plated layer is: 20-25W·min / m. DETAILED DESCRIPTION

[0035] The present invention will be described in more detail below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. The experimental methods in the following examples or comparative examples without specifying specific conditions are generally carried out according to conventional conditions in the art or according to conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets.

[0036] In the following examples or comparative examples:

[0037] The melt index (melt mass flow rate MFR) is determined according to GB / T3682-2018.

[0038] The melt index of the copolymerized polypropylene is 8 g / 10 min (measurement conditions: 230° C., 2.16 kg), and the copolymerized polypropylene is a random ethylene-propylene copolymer.

[0039] The melt index of homopolymer polypropylene is 3.0 g / 10min (measurement conditions: 230 °C, 2.16 kg), and the density is 0.905 g / cm 3 , the isotacticity is 96%.

[0040] The preparation method of the ethylene-propylene-5-vinyl-2-norbornene terpolymer comprises the following steps: using phosphinimine semi-titanocene as a main catalyst, methylaluminoxane as a co-catalyst, and ethylene, propylene and 5-vinyl-2-norbornene as monomers for copolymerization to obtain the ethylene-propylene-5-vinyl-2-norbornene terpolymer.

[0041] The modified pearlescent masterbatch is mixed with 20wt% homopolymer polypropylene and 80wt% modified inorganic filler; the preparation method of the modified inorganic filler is: 4wt% polyethylene glycol monomethyl ether grafted polypropylene copolymer is used as filler surface treatment agent and 96wt% calcium carbonate is used as filler in a high-speed mixer to obtain it.

[0042] The preparation method of polyethylene glycol monomethyl ether grafted polypropylene copolymer comprises the following steps: using a melt grafting method, taking dicumyl peroxide as an initiator and acetone as a solvent, adding the initiator to homopolypropylene, using a high-speed mixer for heating and stirring, grafting maleic anhydride onto the homopolypropylene, and obtaining a maleic anhydride-homopolypropylene grafted copolymer; and then adding the maleic anhydride-homopolypropylene grafted copolymer and polyethylene glycol monomethyl ether into a twin-screw extruder to synthesize the polyethylene glycol monomethyl ether grafted polypropylene copolymer.

[0043] The preparation method of maleic anhydride-homopolypropylene graft copolymer is as follows: using a melt grafting method, dicumyl peroxide is used as an initiator and acetone is used as a solvent, added into homopolypropylene, heated and stirred by a high-speed mixer, maleic anhydride is grafted onto the homopolypropylene, and the maleic anhydride-homopolypropylene graft copolymer is obtained.

[0044] The effective component of the anti-blocking masterbatch is silicon dioxide, and the particle size of silicon dioxide is 4.5 μm.

[0045] Example 1

[0046] This embodiment provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0047] Among them, the formula of each layer is as follows:

[0048] Aluminum-plated layer: 85wt% copolymerized polypropylene and 15wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 4.0 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0049] Middle layer: 73wt% homopolypropylene, 20wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 40%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 7wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 45 g / 10min, and the measurement conditions are: 230℃, 2.16kg);

[0050] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0051] The total thickness of the biaxially oriented polypropylene aluminized label film of this embodiment is 30 μm, the thickness of the aluminized layer is 1.8 μm, and the thickness of the lower surface layer is 1.0 μm.

[0052] This embodiment also provides a method for preparing a biaxially oriented polypropylene aluminized label film, comprising the following steps:

[0053] Step 1: Batching and plasticization: The proportion of each layer of raw materials is set in the control system of the biaxial stretch film production line, and then the batching system will automatically transport the dried raw materials of each layer to each layer extruder according to the input ratio. After melting and plasticizing in each layer extruder, the melt enters the die head through the runner and distributor;

[0054] Step 2: Slice casting: After being extruded through the die, the melt immediately contacts the cooling roller to form a thick sheet;

[0055] Step 3: Longitudinal stretching: The thick sheet is heated to the set temperature by multiple sets of preheating rollers, and then begins to be longitudinally stretched and then shaped;

[0056] Step 4: Transverse stretching: After preheating the thick sheet that has been longitudinally stretched to the set temperature, transverse stretching begins, and after transverse stretching, shaping and cooling are performed;

[0057] Step 5: Traction and reeling: The multi-layer film from the transverse stretching unit enters the traction unit, and after thickness measurement and corona treatment, enters the reeling unit to obtain a parent roll;

[0058] Step 6: Slitting: Slitting the aged mother roll to obtain film rolls of specified width and length.

[0059] In the above process, the melt extrusion temperature of the aluminum-plated layer is 235°C; the melt extrusion temperature of the middle layer and the lower surface layer is 250°C; in the process of the melt contacting the cooling roller, the temperature of the chilling water and the chilling roller is 40°C; the temperature of the longitudinal stretching zone is 125°C; the temperature of the transverse stretching zone is 160°C; the longitudinal stretching ratio is 5.3 times; the transverse stretching ratio is 8.5 times; the corona power factor of the aluminum-plated layer is 23.5W·min / m.

[0060] Example 2

[0061] This embodiment provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0062] Among them, the formula of each layer is as follows:

[0063] Aluminum-plated layer: 80wt% copolymerized polypropylene and 20wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 4.3 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0064] Middle layer: 80wt% homopolypropylene, 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 40%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 5wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 45 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0065] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0066] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this embodiment are the same as those of Embodiment 1.

[0067] The preparation method of the biaxially oriented polypropylene aluminized label film of this embodiment is the same as that of embodiment 1.

[0068] Example 3

[0069] This embodiment provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0070] Among them, the formula of each layer is as follows:

[0071] Aluminum-plated layer: 75wt% copolymerized polypropylene and 25wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 4.5 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0072] Middle layer: 86wt% homopolypropylene, 10wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 40%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 4wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 45 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0073] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0074] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this embodiment are the same as those of Embodiment 1.

[0075] The preparation method of the biaxially oriented polypropylene aluminized label film of this embodiment is the same as that of embodiment 1.

[0076] Comparative Example 1

[0077] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0078] Among them, the formula of each layer is as follows:

[0079] Aluminum-plated layer: 100wt% copolymerized polypropylene;

[0080] Middle layer: 80wt% homopolypropylene, 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 40%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 5wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 45 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0081] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0082] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0083] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0084] Comparative Example 2

[0085] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0086] Among them, the formula of each layer is as follows:

[0087] Aluminum-plated layer: 90wt% copolymerized polypropylene and 10wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 4.3 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0088] Middle layer: 80wt% homopolypropylene, 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 40%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 5wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 45 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0089] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0090] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0091] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0092] Comparative Example 3

[0093] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0094] Among them, the formula of each layer is as follows:

[0095] Aluminum-plated layer: 70wt% copolymerized polypropylene and 30wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 4.3 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0096] Middle layer: 80wt% homopolypropylene, 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 40%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 5wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 45 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0097] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0098] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0099] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0100] Comparative Example 4

[0101] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0102] Among them, the formula of each layer is as follows:

[0103] Aluminum-plated layer: 80wt% copolymerized polypropylene and 20wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 2.0 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0104] Middle layer: 80wt% homopolypropylene, 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 40%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 5wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 45 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0105] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0106] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0107] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0108] Comparative Example 5

[0109] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0110] Among them, the formula of each layer is as follows:

[0111] Aluminum-plated layer: 80wt% copolymerized polypropylene and 20wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 6 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0112] Middle layer: 80wt% homopolypropylene, 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 40%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 5wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 45 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0113] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0114] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0115] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0116] Comparative Example 6

[0117] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0118] Among them, the formula of each layer is as follows:

[0119] Aluminum-plated layer: 80wt% copolymerized polypropylene and 20wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 4.3 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0120] Middle layer: 80wt% homopolypropylene, 15wt% conventional pearlescent masterbatch (low molecular weight ester as surface modifier, calcium carbonate particle size of 1.0μm, melt index of 15 g / 10min, measurement conditions: 230℃, 2.16kg) and 5wt% maleic anhydride-homopolypropylene graft copolymer (melt index of 45 g / 10min, measurement conditions: 190℃, 2.16kg);

[0121] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0122] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0123] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0124] Comparative Example 7

[0125] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0126] Among them, the formula of each layer is as follows:

[0127] Aluminum-plated layer: 80wt% copolymerized polypropylene and 20wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4, the content of 5-vinyl-2-norbornene is 4.3 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0128] Middle layer: 80wt% homopolypropylene, 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 30%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 5wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 45 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0129] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0130] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0131] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0132] Comparative Example 8

[0133] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0134] Among them, the formula of each layer is as follows:

[0135] Aluminum-plated layer: 80wt% copolymerized polypropylene and 20wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 4.3 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0136] Middle layer: 80wt% homopolypropylene, 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 50%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 5wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 45 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0137] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0138] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0139] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0140] Comparative Example 9

[0141] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0142] Among them, the formula of each layer is as follows:

[0143] Aluminum-plated layer: 80wt% copolymerized polypropylene and 20wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 4.3 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0144] Middle layer: 85wt% homopolymer polypropylene and 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 50%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg);

[0145] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0146] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0147] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0148] Comparative Example 10

[0149] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0150] Among them, the formula of each layer is as follows:

[0151] Aluminum-plated layer: 80wt% copolymerized polypropylene and 20wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4, the content of 5-vinyl-2-norbornene is 4.3 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0152] Middle layer: 83wt% homopolypropylene, 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 40%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 2wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 45 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0153] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0154] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0155] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0156] Comparative Example 11

[0157] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0158] Among them, the formula of each layer is as follows:

[0159] Aluminum-plated layer: 80wt% copolymerized polypropylene and 20wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 4.3 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0160] Middle layer: 76wt% homopolypropylene, 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 40%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 9wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 45 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0161] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0162] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0163] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0164] Comparative Example 12

[0165] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0166] Among them, the formula of each layer is as follows:

[0167] Aluminum-plated layer: 80wt% copolymerized polypropylene and 20wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 4.3 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0168] Middle layer: 80wt% homopolypropylene, 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 50%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 5wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 30 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0169] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0170] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0171] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0172] Comparative Example 13

[0173] The comparative example provides a biaxially oriented polypropylene aluminized label film, comprising an aluminized layer, an intermediate layer and a lower surface layer which are arranged in sequence.

[0174] Among them, the formula of each layer is as follows:

[0175] Aluminum-plated layer: 80wt% copolymerized polypropylene and 20wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer (melt index 10g / 10min, measurement conditions: 230℃, 2.16kg; melting point 115℃, number average molecular weight 4×10 4 , the content of 5-vinyl-2-norbornene is 4.3 mol%, the content of ethylene accounts for 4 mol% of the total content of ethylene and propylene, and the content of propylene accounts for 96 mol%);

[0176] Middle layer: 80wt% homopolypropylene, 15wt% modified pearlescent masterbatch (the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 50%, the particle size of calcium carbonate is 1.0μm, the melt index is 16 g / 10min, and the measurement conditions are: 230℃, 2.16kg) and 5wt% maleic anhydride-homopolypropylene graft copolymer (melt index is 70 g / 10min, and the measurement conditions are: 190℃, 2.16kg);

[0177] Lower surface layer: 97wt% homopolymer polypropylene and 3wt% anti-blocking masterbatch.

[0178] The total thickness and thickness of each layer of the biaxially oriented polypropylene aluminized label film of this comparative example are the same as those of Example 1.

[0179] The preparation method of the biaxially oriented polypropylene aluminized label film of this comparative example is the same as that of Example 1.

[0180] Performance Evaluation

[0181] The following performance evaluations were performed on the biaxially oriented polypropylene aluminized label films of Examples 1-3 and Comparative Examples 1-13, respectively. The performance evaluation results are shown in Tables 1 and 2:

[0182] Tensile strength: tested according to GB / T1040.3;

[0183] Production smoothness (qualitative): membrane rupture;

[0184] Surface tension and durability of the aluminum-platable layer: The films prepared in Examples 1-3 and Comparative Examples 1-13 were subjected to aging treatment for 0 days, 30 days, 60 days and 90 days, and the surface tension of the aluminum-platable layer of the films was tested. The surface tension was tested according to GB / T2913.

[0185] Surface tension and durability of the aluminum layer: The films prepared in Examples 1-3 and Comparative Examples 1-13 were aluminum-plated (vacuum evaporation) to form an aluminum layer on the surface of the aluminum-platable layer. After aging treatment for 0 days, 30 days, 60 days and 90 days, the surface tension of the aluminum layer was tested. The surface tension was tested according to GB / T2913.

[0186] Table 1 Film performance evaluation results

[0187]

[0188] Table 2 Performance evaluation results of thin film after aluminum plating

[0189]

[0190] Please refer to Table 1 and Table 2. The biaxially oriented polypropylene aluminized label films of Examples 1-3 of the present invention have a durable surface tension of the aluminized layer, and the aluminum layer formed after aluminum plating on the surface of the aluminized layer has strong adhesion, and there is no problem of loose adhesion and aluminum falling off of the aluminum layer. Furthermore, after the aluminum layer is firmly adhered, the aluminum layer does not undergo corona attenuation, and will not affect subsequent coating, printing and other processes.

[0191] In the biaxially oriented polypropylene aluminized label film of Comparative Example 1, the aluminized layer only contains copolymerized polypropylene, and no ethylene-propylene-5-vinyl-2-norbornene terpolymer is added to the aluminized layer. The surface tension and durability of the aluminized layer of the film cannot be significantly improved, and the aluminized layer is insufficient to effectively block the migration of substances in the intermediate layer. The surface tension of the aluminum layer formed after aluminizing the surface of the aluminized layer of the film is not durable.

[0192] In the biaxially oriented polypropylene aluminized label film of Comparative Example 2, the content of the ethylene-propylene-5-vinyl-2-norbornene terpolymer added to the aluminized layer is too low, and the aluminized layer of the film has little effect in blocking the migration of substances in the intermediate layer and improving the surface tension and durability of the aluminized layer. The surface tension of the aluminum layer formed after aluminizing the surface of the aluminized layer of the film is not durable.

[0193] In the biaxially oriented polypropylene aluminized label film of Comparative Example 3, the content of ethylene-propylene-5-vinyl-2-norbornene terpolymer added to the aluminized layer is too high. The excessive introduction of ring structure will increase the steric hindrance effect of the copolymerized polypropylene molecular chain, restricting the movement of the molecular chain and reducing the mechanical properties of the film.

[0194] In the biaxially oriented polypropylene aluminized label film of Comparative Example 4, the content of 5-vinyl-2-norbornene in the ethylene-propylene-5-vinyl-2-norbornene terpolymer added to the aluminized layer is too low, which cannot achieve the effect of improving the performance of the aluminized layer in blocking the migration of intermediate layer substances. The surface tension and durability of the aluminum layer formed after aluminizing the surface of the aluminized layer of the film cannot be significantly improved.

[0195] In the biaxially oriented polypropylene aluminized label film of comparative example 5, the content of 5-vinyl-2-norbornene in the ethylene-propylene-5-vinyl-2-norbornene terpolymer added to the aluminized layer is too high. Due to the rigid structure of norbornene, too much norbornene will make the polypropylene film brittle, resulting in a decrease in the mechanical properties of polypropylene.

[0196] In the biaxially oriented polypropylene aluminized label film of Comparative Example 6, the pearlescent masterbatch added in the middle layer is a conventional pearlescent masterbatch, and the conventional pearlescent masterbatch uses a low-molecular ester as a surface modifier to coat the surface of calcium carbonate; the low-molecular ester in the middle layer easily migrates to the surface of the aluminizable layer and easily covers the polar groups on the surface of the aluminizable layer, resulting in insufficient surface tension persistence of the aluminizable layer of the film itself and the aluminum layer formed after aluminum plating on the surface of the aluminized layer.

[0197] In the biaxially oriented polypropylene aluminized label film of Comparative Example 7, the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer of the modified pearlescent masterbatch added to the middle layer is too low, and it cannot maintain the surface tension of the aluminizable layer of the film itself and the aluminum layer formed after aluminizing the surface of the aluminized layer for a long time.

[0198] In the biaxially oriented polypropylene aluminized label film of Comparative Example 8, the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer of the modified pearlescent masterbatch added in the middle layer is too high, and the polyethylene glycol monomethyl ether chain segment will destroy the original molecular chain arrangement and crystal structure of the copolymerized polypropylene, resulting in a decrease in the mechanical properties of the film.

[0199] The biaxially oriented polypropylene aluminized label film of Comparative Example 9 contains only homopolymer polypropylene and modified pearlescent masterbatch in the middle layer, and no maleic anhydride-polypropylene graft copolymer is added to the middle layer, which fails to improve the dispersibility of the modified pearlescent masterbatch in the homopolymer polypropylene and the effect of improving the mechanical properties.

[0200] In the biaxially oriented polypropylene aluminized label film of Comparative Example 10, the content of the maleic anhydride-polypropylene graft copolymer added in the middle layer is too low, and the effect of improving the mechanical properties of the film is not obvious.

[0201] In the biaxially oriented polypropylene aluminum-plated label film of Comparative Example 11, the content of maleic anhydride-polypropylene graft copolymer added in the middle layer is too high, and the molecular chains of the substances in the middle layer will be entangled to a certain extent, causing the shear viscosity of the melt to increase, affecting the smoothness of production.

[0202] In the biaxially oriented polypropylene aluminized label film of Comparative Example 12, the melt index of the maleic anhydride-polypropylene graft copolymer added to the middle layer is too low, and the modified pearlescent masterbatch is unevenly dispersed, resulting in a decrease in mechanical strength.

[0203] In the biaxially oriented polypropylene aluminized label film of Comparative Example 13, the melt index of the maleic anhydride-polypropylene graft copolymer added in the middle layer is too high, which is not conducive to the uniform distribution of the modified pearlescent masterbatch in the homopolymer polypropylene, and easily causes a decrease in the mechanical properties at local locations, affecting the smoothness of production.

[0204] The above-mentioned embodiments only express several implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the invention patent. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and the present invention is also intended to include these modifications and modifications.

Claims

1. A biaxially oriented polypropylene aluminized label film, characterized in that: It includes an aluminum-platable layer, an intermediate layer and a lower surface layer arranged in sequence; The aluminum-platable layer comprises copolymerized polypropylene and 15-25wt% ethylene-propylene-5-vinyl-2-norbornene terpolymer; the content of 5-vinyl-2-norbornene in the ethylene-propylene-5-vinyl-2-norbornene terpolymer is 4.0-4.5mol%; the number average molecular weight of the ethylene-propylene-5-vinyl-2-norbornene terpolymer is (2.5-5)×10 4 ; The intermediate layer comprises homopolypropylene, 10-20wt% modified pearlescent masterbatch and 4-7wt% maleic anhydride-homopolypropylene graft copolymer; the modified pearlescent masterbatch comprises homopolypropylene and 75-85wt% modified inorganic filler; the modified inorganic filler is obtained by coating the surface of calcium carbonate with polyethylene glycol monomethyl ether grafted polypropylene copolymer, the polyethylene glycol monomethyl ether grafted polypropylene copolymer is synthesized from maleic anhydride-homopolypropylene graft copolymer and polyethylene glycol monomethyl ether, and the grafting rate of polyethylene glycol monomethyl ether in the polyethylene glycol monomethyl ether grafted polypropylene copolymer is 35-45%; the melt index of the maleic anhydride-homopolypropylene graft copolymer at 230°C and a load of 2.16kg is 40-50g / 10min.

2. The biaxially oriented aluminized polypropylene label film according to claim 1, characterized in that: In the aluminum-platable layer, the preparation method of the ethylene-propylene-5-vinyl-2-norbornene terpolymer is as follows: using phosphinimine semi-titanocenes as a main catalyst, methylaluminoxane as a co-catalyst, and ethylene, propylene and 5-vinyl-2-norbornene as monomers for copolymerization to obtain the ethylene-propylene-5-vinyl-2-norbornene terpolymer.

3. The biaxially oriented aluminized polypropylene label film according to claim 1, characterized in that: In the aluminum-platable layer, the melt index of the ethylene-propylene-5-vinyl-2-norbornene terpolymer at 230° C. and a load of 2.16 kg is 8-12 g / 10 min; the melting point of the ethylene-propylene-5-vinyl-2-norbornene terpolymer is 108-120° C.

4. The biaxially oriented aluminized polypropylene label film according to claim 1, characterized in that: In the aluminum-platable layer, the copolymerized polypropylene has a melting index of 6-10 g / 10 min at 230° C. and a load of 2.16 kg.

5. The biaxially oriented aluminized polypropylene label film according to claim 1, characterized in that: In the middle layer, the polyethylene glycol monomethyl ether grafted polypropylene copolymer is prepared by adding maleic anhydride-homopolymerized polypropylene grafted copolymer and polyethylene glycol monomethyl ether into a twin-screw extruder to synthesize the polyethylene glycol monomethyl ether grafted polypropylene copolymer.

6. The biaxially oriented aluminized polypropylene label film according to claim 1, characterized in that: The preparation method of the maleic anhydride-homopolypropylene graft copolymer in the synthetic raw material of the maleic anhydride-homopolypropylene graft copolymer in the intermediate layer and / or the polyethylene glycol monomethyl ether graft polypropylene copolymer is as follows: using a melt grafting method, dicumyl peroxide is used as an initiator and acetone is used as a solvent, which is added to homopolypropylene, and heated and stirred by a high-speed mixer to graft maleic anhydride onto the homopolypropylene to obtain the maleic anhydride-homopolypropylene graft copolymer.

7. The biaxially oriented aluminized polypropylene label film according to claim 1, characterized in that: In the intermediate layer, the modified inorganic filler in the modified pearlescent masterbatch is prepared by treating 3-5wt% polyethylene glycol monomethyl ether grafted polypropylene copolymer as a filler surface treatment agent and 95-97wt% calcium carbonate as a filler in a high-speed mixer; the particle size of the calcium carbonate is 0.5-1.5μm.

8. The biaxially oriented aluminized polypropylene label film according to claim 1, characterized in that: In the middle layer, the homopolypropylene has a melting index of 3-8 g / 10 min at 230° C. and a load of 2.16 kg; and the modified pearlescent masterbatch has a melting index of 14-18 g / 10 min at 230° C. and a load of 2.16 kg.

9. A method for preparing a biaxially oriented polypropylene aluminized label film according to any one of claims 1 to 8, characterized in that: The following steps are involved: Step 1: Batching and plasticization: The proportion of each layer of raw materials is set in the control system of the biaxial stretch film production line, and then the batching system will automatically transport the dried raw materials of each layer to each layer extruder according to the input ratio. After melting and plasticizing in each layer extruder, the melt enters the die head through the runner and distributor; Step 2: Slice casting: After being extruded through the die, the melt immediately contacts the cooling roller to form a thick sheet; Step 3: Longitudinal stretching: The thick sheet is heated to the set temperature by multiple sets of preheating rollers, and then begins to be longitudinally stretched and then shaped; Step 4: Transverse stretching: After preheating the thick sheet that has been longitudinally stretched to the set temperature, transverse stretching begins, and after transverse stretching, shaping and cooling are performed; Step 5: Traction and reeling: The multi-layer film from the transverse stretching unit enters the traction unit, and after thickness measurement and corona treatment, enters the reeling unit to obtain a parent roll; Step 6: Slitting: Slitting the aged mother roll to obtain film rolls of specified width and length.

Citation Information

Patent Citations

  • Antibacterial PP spun-bonded non-woven fabric and preparation method thereof

    CN113106633A

  • Low-temperature anti-wrinkle biaxially oriented polypropylene label film and preparation method thereof

    CN119141995A